Tuning Stoichiometry and Structure of Pd-WO(3−x) Thin Films for Hydrogen Gas Sensing by High-Power Impulse Magnetron Sputtering - Kumar, Nirmal (Materials (Basel), 2020)
By tuning the deposition parameters of reactive high-power impulse magnetron sputtering, specifically the pulse length, we were able to prepare WO(3−x) films with various stoichiometry and structure. Subsequently, the films were annealed in air at moderate temperature (350 °C). We demonstrate that the stoichiometry of the as-deposited films influences considerably the type of crystalline phase formed in the annealed films. The appropriate sub-stoichiometry of the films (approx. WO(2.76)) enabled crystallization of the monoclinic phase during the annealing. This phase is favorable for hydrogen sensing applications. To characterize the sensory behavior of the films, the tungsten oxide films were decorated by Pd nanoparticles before annealing and were assembled as a conductometric gas sensor. The sensory response of the films that crystallized in the monoclinic structure was proven to be superior to that of the films containing other phases.